Kokemuksia fysiikan opiskelun haasteellisuudesta Jyväskylän yliopiston fysiikan laitoksella - Huuhka, Niilo (2024)
In this thesis difficulties in university level physics studies are investigated. Students’ personal experiences and opinions on both physics and studying physics as a subject were collected. Ten physics major students were interviewed to gather the data during the winter and spring of 2024. Central themes in the thesis are difficulties in studying physics, how students cope with these difficulties, and how students are evaluated during their studies. Many difficulties related to physics studies were discovered, of which most impactful were those related to mathematics education, fast pace of physics education, the lack of learning support and unsuitable evaluation methods. The research showed that physics education could be improved by increasing support for students, and developing and expanding mathematical education at the Department of Physics to enhance students’ ability to apply the acquired mathematical knowledge on physics courses. Evaluation should move away from heavy emphasis on exams and increase the usage of diverse evaluation methods and long-term assessment, as to better reflect work life skills of physicists. These improvements would also encourage students to study for meaningful competence instead of focusing on achieving desired grades.